Companion(s) of the Eclipsing Binary KIC 3832716. Issue Volume 14:Issue S339(2018) (November 2017) - Parimucha, Š.; Fedurco, M.; Gajdoš, P.
Abstract: Detailed analyses of observations by the Kepler satellite may reveal unknown facts about objects that were previously regarded as eclipsing binaries. We present results of our analysis of such an object, KIC 3832716. We show that the system actually contains two eclipsing binaries ( EB1 and EB2 ), with orbital periods of 1.14 and 2.17 days, orbiting around their common centre of mass with period of at least 1400 days and with an estimated mass ratio of 0.7 ± 0.3. Analyses of the (O–C) diagrams of both eclipsing pairs show three different types of variation: (i) long-term changes probably due to light-time effects, (ii) spikes caused by the superposition of the eclipses of both binaries, and (iii) semi-regular variations in EB1 with a period of 57 days, presumably caused by the presence of spots on its secondary component.